Urban Legacy of Berlin - Chaowarat, Pondej (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This article examines the urban legacy of Berlin in two areas: 1) the urban form used as a design guideline for Urban Renewal since the German Unification in 1989, originating from the Industrial Revolution era, and 2) Guidelines for public consultation, which are used in the urban renewal process. The study found that the particular urban form promoted as unique to Berlin consists of 1) tenement houses in height unexceeded 22 meters, with a façade of natural stone 2) corridor streets and 3) public squares. The emulation of its urban legacy through urban renewal reinforces and accentuates Berlin’s urban identity. As for the second issue, the public consultation appears in urban renewal processes in Berlin in a variety of forms and covers a wide range of levels. Examples of such activities are the special committee, the public hearing and the presentation of the results of design competitions through various public media. Such procedures initiate dialogues among people which shape public understanding, awareness of a project’s importance and also its acceptance; and eventually successful urban renewal with a balance of physical, economic and social aspects.